El héroe. Literatura y psicología analítica. - Rodríguez Zamora, José Miguel (2012)
This article presents an approximation to the myth of the hero, fundamental within the literary discourse, from the analytical psychology proposed by Carl Jung. It discusses its origin, its development and its literary consequences as a functional archetype of the narrative.